The role of green productivity strategy in achieving sustainability of environmental and social performance - Daoud, Fadila Salman (Journal of Economic, Administrative and Legal Sciences, 2017)
Companies seek among the main strategies that achieve sustainability, environmental and social performance, and this can only be achieved through the realization of green productivity, so the study aims to highlight the green productivity strategy standards and how they can play a significant role in environmental sustainability, as it is the last of topical subjects as the interest in it will lead to the shed and the concentration of industrial and consumer organizations to protect the environment through the output of green product cultural awareness of the workers and the community, which means that green productivity will lead organizations to achieve competitive advantage in the competitive environment. So was applied checklist through field homeliness and personal interviews, a number of department managers (environment, quality and safety, as well as the drilling sites). The study found that although the in spite of the arrival of the Iraqi Drilling Company to apply some standards and to varying degrees, but it sustainability did not achieve environmental and social performance. This leads us to not accept the main assumption. There is a role and impact for the green productivity strategy in sustainability for environmental and social performance.